Heterogeneity of laser‐irradiated films of polyvinyl alcohol/starch blends: effect of glycerol content. (10th January 2013) - Sreekumar, P. A.; Al‐Harthi, Mamdouh A.; Gondal, M. A.; De, S. K.
ABSTRACT The present paper reports the results of studies on the effect of laser irradiation on the morphology and thermal properties of starch/polyvinyl alcohol (PVA) blend, with varying glycerol concentration. Differential scanning calorimeter results showed that laser irradiation increased the heat of fusion (ΔHfus), heat of crystallization (ΔHcry), temperature of melting (Tm), temperature of crystallization (Tcry) and percentage crystallinity as a function of the amount of glycerol. It is believed that breakdown of the intermolecular hydrogen bonding between the starch and PVA causes an increase in the blend heterogeneity. These results are corroborated with the findings from thermogravimetric analysis and scanning electron microscope images. Copyright © 2013 John Wiley & Sons, Ltd.